Fungal infections of the small and large intestine. Issue 9 (September 1992) - Prescott, R J; Harris, M; Banerjee, S S
Abstract : AIMS: To study the pathological features of fungal infections affecting the lower intestinal tract (duodenum, small and large bowels). METHODS: Between mid-1981 and mid-1991, 14 cases of deep mycotic infections affecting the lower intestinal tract were found among 890 consecutive necropsies on patients with malignant disease treated in a regional cancer centre (incidence 1.6%). These 14 cases accounted for 54% of all gastrointestinal fungal infection detected. The relevant clinical, necropsy, histological and microbiological data were reviewed. RESULTS: Candida spp and Aspergillus spp accounted for all infections. The macroscopic appearances included ulcers of varying configuration, mucosal flecks, sloughed mucous membranes, polypoid masses and segmental lesions. Either organism could produce this range of lesions, but Candida tended to have a mucosal location and Aspergillus was associated with transmural invasion. Combined infections showed Candida in the surface mucosa and Aspergillus hyphae in submucosal vessels with spread into the bowel wall in a radiating pattern. During the final illness, gastrointestinal symptoms and signs were often slight and microbiological investigations were unhelpful. CONCLUSIONS: Variable gross appearances are relevant for endoscopists, particularly lesions which resemble pseudomembranous colitis. Endoscopic biopsy specimens may have a role in antemortem diagnosis. Failure to diagnose these infections during life emphasises the importance of necropsy in the clinicopathological audit of deaths in this group of patients.